Croatia : Kortars horvat Müvészet. - Ernst Museum, Budapest (Budapest : Mücsarnok, 1992)
Kozaric, Ivan ; Knifer, Julije ; Ivekovic, Sanja ; Martinis, Dalibor ; Bucan, Boris ; Gudac, Vladimir ; Kipke, Zeljko ; Juric, Dusan ; Schubert, Edita ; Rakoci, Dubravka ; Pokas, Vesna ; Petercol, Goran ; Rasic, Ante ; Drinkovic, Slavomir ; Jandric, Dorde ; Stipesevic, Krunoslav ; Zuvela, Gorki
Croatia : Kortars horvat Müvészet, Ernst Múzeum, február 20 - március 22, 1992
boek